2011
DOI: 10.1016/j.neurobiolaging.2010.03.017
|View full text |Cite
|
Sign up to set email alerts
|

White matter integrity correlates of implicit sequence learning in healthy aging

Abstract: Previous research has identified subcortical (caudate, putamen, hippocampus) and cortical (dorsolateral prefrontal cortex, DLPFC; frontal motor areas) regions involved in implicit sequence learning, with mixed findings for whether these neural substrates differ with aging. The present study used diffusion tensor imaging (DTI) tractography to reconstruct white matter connections between the known gray matter substrates, and integrity of these tracts was related to learning in the alternating serial reaction tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
93
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(110 citation statements)
references
References 45 publications
12
93
0
1
Order By: Relevance
“…15), suggesting that our scan length is sufficient. Second, our sample size is relatively small, although comparable (or larger) than that of other published studies using similar tasks (e.g., Bennett et al, 2011;Rieckmann et al, 2010;Schendan et al, 2003;Simon et al, 2012). Since the chances of Type I error increase in small samples, however, replication with a larger sample is desirable, and future studies focusing on individual differences should consider acquiring longer scans.…”
Section: Limitations and Future Directionsmentioning
confidence: 92%
See 2 more Smart Citations
“…15), suggesting that our scan length is sufficient. Second, our sample size is relatively small, although comparable (or larger) than that of other published studies using similar tasks (e.g., Bennett et al, 2011;Rieckmann et al, 2010;Schendan et al, 2003;Simon et al, 2012). Since the chances of Type I error increase in small samples, however, replication with a larger sample is desirable, and future studies focusing on individual differences should consider acquiring longer scans.…”
Section: Limitations and Future Directionsmentioning
confidence: 92%
“…This is not surprising in light of evidence indicating that a direct anatomical connection is not necessary for functional connectivity in the resting state (Honey et al, 2009). For SL, our earlier work using DTI tractography suggests that this DC-MTL functional relationship may be mediated via connections with the dorsolateral prefrontal cortex (DLPFC) (Bennett et al, 2011). Early in training, SL scores were positively correlated with the microstructural integrity of the tract between the right MTL and DLPFC, while later in training, learning scores positively correlated with the integrity of left caudate to DLPFC tract.…”
Section: Stillman Et Almentioning
confidence: 92%
See 1 more Smart Citation
“…On the one hand it could be argued that changes in prediction error signaling in OA are due to compromised dopamine (DA) projections to frontostriatal circuits (Dreher et al, 2008). On the other hand, there is also evidence for the idea that age-related changes in prediction error signals result from deficits in the connectivity between frontal and striatal regions in OA (Bennett et al, 2011;SamanezLarkin et al, 2012). Moreover, findings from multimodal imaging (positron emission tomography with fMRI) studies showed that striatal DA also affects frontal working memory and cognitive control functions (Braskie et al, 2008;Landau et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a recent study showed that white matter integrity of the dentato-thalamo-cortical tract, connecting the lateral cerebellum to motor and prefrontal areas, is associated with motor sequence learning (Schulz Wessel, Zimerman, Timmermann, Gerloff, & Hummel, 2015). In addition, it has been shown that white matter integrity of these circuits predicts performance during implicit motor learning (Bennett, Madden, Vaidya, Howard, & Howard, 2011), which may lead to the suggestion that youth elite soccer players have better connectivity in these circuits. Our results are in line with studies on brain structure and functioning in experts on sports and music (Chang, 2014;Nakata et al, 2010;Roberts et al, 2012;Wei & Luo, 2010), supporting the relationship between general brain plasticity, motor learning skills and expertise.…”
Section: Discussionmentioning
confidence: 99%